2019
DOI: 10.3892/ijmm.2019.4413
|View full text |Cite
|
Sign up to set email alerts
|

A novel small molecule compound VCP979 improves ventricular remodeling in murine models of myocardial ischemia/reperfusion injury

Abstract: Persistent ventricular remodeling following myocardial ischemia/reperfusion (MI/R) injury results in functional decompensation and eventual progression to heart failure. VcP979, a novel small-molecule compound developed in-house, possesses anti-inflammatory and anti-fibrotic activities. In the present study, no significant pathological effect was observed following the administration of VCP979 on multiple organs in mice and no difference of aspartate transaminase/alanine aminotransferase/lactate dehydrogenase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Mice were anesthetized with 2% isoflurane inhalation and analyzed using a Vevo 2100 high-resolution imaging system with a 30-MHz linear transducer (FUJIFILM Visual-Sonics, Inc.) as previously described [ 11 ]. We acquired and analyzed the cardiac function of each group through long-axis scans using M-mode images including left ventricular ejection function (LVEF), left ventricular fractional shortening (LVFS), left ventricular end diastolic/systolic volume (LVEDV/LVESV) and left ventricular end diastolic/systolic diameter (LVEDD/LVESD) both on day 7 and 28.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were anesthetized with 2% isoflurane inhalation and analyzed using a Vevo 2100 high-resolution imaging system with a 30-MHz linear transducer (FUJIFILM Visual-Sonics, Inc.) as previously described [ 11 ]. We acquired and analyzed the cardiac function of each group through long-axis scans using M-mode images including left ventricular ejection function (LVEF), left ventricular fractional shortening (LVFS), left ventricular end diastolic/systolic volume (LVEDV/LVESV) and left ventricular end diastolic/systolic diameter (LVEDD/LVESD) both on day 7 and 28.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were anesthetized with 2% iso urane inhalation and analyzed using a Vevo 2100 high-resolution imaging system with a 30-MHz linear transducer (FUJIFILM Visual-Sonics, Inc.) as previously described [11]. We acquired and analyzed the cardiac function of each group through long-axis scans using M-mode images including left ventricular ejection function (LVEF), left ventricular fractional shortening (LVFS), left ventricular end diastolic/systolic volume (LVEDV/LVESV) and left ventricular end diastolic/systolic diameter (LVEDD/LVESD) on day 7 and 28.…”
Section: Echocardiographymentioning
confidence: 99%
“…Li et al revealed that losartan, an angiotensin II (Ang II) receptor blocker acting on the Ang II type-1 receptor (AT1R) subtype, protects against myocardial I/R injury via vascular integrity preservation [42]. Liu et al showed that inhibiting Ang II can improve ventricular remodeling in murine models of myocardial I/R injury [43]. These indicate that maintaining a steady state of Ang II levels is a potential strategy for treating myocardial I/R injury.…”
Section: Discussionmentioning
confidence: 99%